Case report: Efficacy analysis of radiofrequency catheter ablation combined with atrial appendage resection for atrial tachycardia originating from the atrial appendage in children - Liu, Jing; Cao, Xiaoxiao; Li, Changjian; Feng, Xiaoyuan; Sun, Dongming; Zhang, Yong (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the efficacy of radiofrequency catheter ablation (RFCA) combined with atrial appendage (AA) resection to treat atrial tachycardia (AT) originating from the AA in children. Methods: Three children with AT originating from the AA were diagnosed using the Ensite three-dimensional electroanatomic mapping system. Clinical features and electrocardiographic (ECG) manifestations were analyzed. Ablations were performed using a cold saline-infused catheter at appendages targeting loci of AT origin under the guidance of the Ensite system. Atrial appendage resection was performed in combination with cardiac surgery and the curative effect was evaluated. Results: The ages of the three patients were 3.5, 5.75, and 12.9 years. Two cases originated from the right atrial appendage (RAA) and one originated from the left atrial appendage (LAA). The ECG characteristics of AT from the RAA were as follow: (1) negative P waves in lead V1; (2) positive P waves in leads Ⅱ, Ⅲ, and aVF; (3) positive P wave in lead Ⅰ with varying shapes in lead aVL; (4) prolonged PR interval with no QRS wave after some P waves. The ECG of the LAA was characterized by: (1) positive P waves in lead V1 with a bimodal pattern; (2) positive P waves in leads Ⅱ, Ⅲ, and aVF; and (3) negative P waves in leads Ⅰ and aVL. Preoperative echocardiography showed cardiac enlargement and decreased left ventricular ejection fraction (LVEF) in all 3 cases. One case was cured after RFCA, and the remaining 2 cases required AA resection after RFCA. No recurrence was detected at 1-18 months of follow-up, and the left ventricular end-diastolic diameter and LVEF returned to normal. Conclusions: Atrial tachycardia originating from the AA in children showed characteristic P-wave presentation on ECG, and sustained episodes of AT resulted in tachycardia-induced cardiomyopathy. Children who are not successful controled by RFCA, or who have recurrence after RFCA, could benifit from AA resection.